2013
DOI: 10.1186/1748-717x-8-238
|View full text |Cite
|
Sign up to set email alerts
|

Phase II clinical trial of whole-brain irradiation plus three-dimensional conformal boost with concurrent topotecan for brain metastases from lung cancer

Abstract: BackgroundPatients with brain metastases from lung cancer have poor prognoses and short survival time, and they are often excluded from clinical trials. Whole-cranial irradiation is considered to be the standard treatment, but its efficacy is not satisfactory. The purpose of this phase II clinical trial was to evaluate the preliminary efficacy and safety of the treatment of whole-brain irradiation plus three-dimensional conformal boost combined with concurrent topotecan for the patients with brain metastases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
0
17
1
Order By: Relevance
“…[ 11 12 13 ] However, the results from other studies have not found that systemic therapy has clinical benefits. [ 14 15 16 17 ] Studies involving patients with a limited number of intracranial lesions are limited. The Radiation Therapy Oncology Group (RTOG) 0320 study is a randomized study to explore whether systemic therapy after radiotherapy can improve OS in NSCLC patients with 1–3 BMs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 12 13 ] However, the results from other studies have not found that systemic therapy has clinical benefits. [ 14 15 16 17 ] Studies involving patients with a limited number of intracranial lesions are limited. The Radiation Therapy Oncology Group (RTOG) 0320 study is a randomized study to explore whether systemic therapy after radiotherapy can improve OS in NSCLC patients with 1–3 BMs.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of efficacy was carried out according to the Response Evaluation Criteria In Solid Tumors (RECIST) 1.1 standards [ 11 ]. Symptoms of brain metastases were evaluated according to the neurologic function score (NFS):[ 12 ] score 0, no neurologic symptoms; score 1, minor neurologic symptoms; score 2, moderate neurologic symptoms, fully active; score 3, moderate to severe neurologic symptoms, less than fully active; and score 4, severe neurologic symptoms, inactive.…”
Section: Methodsmentioning
confidence: 99%
“…Topotecan has shown activity in treatment of breast cancer 2,3 . In preclinical and clinical studies, TOPO has demonstrable radiation‐sensitizing effects in multiple solid tumor histologies, including breast carcinoma, 10,11 and in patients with brain metastases 10,12,13 . Although the mechanism is unclear, the radiosensitizing effect may relate to accumulation of cells in S phase and inhibition of DNA repair 10 .…”
Section: Discussionmentioning
confidence: 99%